Evaluation Of Factors Affecting The Cell Suspension Cultures And The Production Of Bioactive Compounds Of Spilanthes Acmella L - Lim , Fung Hui (2010)

(untitled)
In this study, five lines of the callus culture were established from the petioles of Spilanthes acmella L. The culture was initiated on callus induction medium, Murashige and Skoog (MS) medium supplemented with 0.5 mg/L 2, 4-D. The petiole explants were also cultured on MS medium with 0.5 mg/L 2, 4-D and different concentrations of picloram (0.0 – 2.0 mg/L). Callus initiated on the medium with the presence of picloram induced lesser callus when compared with the callus initiated with only 2, 4-D. Compact and granular calluses were continuously produced with each subculture cycle.